THE STRATEGY OF CREATING EMPLOYMENT THROUGH LOCAL ECONOMIC DEVELOPMENT WITH HEXAGONAL APPROACH IN TALISAYAN DISTRICT OF BERAU REGENCY - Ganie, Djupiansyah; Hasyim, Wahid; Umam, Khairul (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
This study was conducted in 10 villages in the district of Talisayan with the object of Community business potential. The goal of this study is to identify the potential resource of the local economy that highly attractive, competitive and potentially to create jobs. Data were collected through focus group discussion with the community. The analysis method used is descriptive qualitative analysis. The results showed that the economically productive featured most likely to create jobs is trade, home industry and services and agriculture, and will be more optimal if it is Synergized with the Heksagonal Approach